Ropivacaine epidural anesthesia and analgesia versus general anesthesia and intravenous patient-controlled analgesia with morphine in the perioperative management of hip replacement: Ropivacaine hip replacement multicenter study group - Wulf, Hinnerk; Biscoping, Jürgen; Beland, Barbara; Bachmann-Mennenga, Bernd; Motsch, Johann (Anesthesia & analgesia, 1999)
The aim of our study was to compare epidural anesthesia and analgesia (EDA) with ropivacaine versus general anesthesia followed by IV patient-controlled analgesia with morphine (GA/PCA) after hip replacement regarding pain, side effects, and discharge from the postanesthesia care unit. After ethics committee approval, randomization, and informed consent, 90 patients were enrolled. In Group EDA, epidural anesthesia (ropivacaine 10 mg/mL, 15-25 mL) was followed by an epidural infusion (2 mg/mL, 4-6 mL/h for 24 h, plus top-up doses of 6-10 mL for 48 h). GA/PCA patients received general anesthesia (isoflurane/N2O/fentanyl) followed by IV patient-controlled analgesia with morphine postoperatively. Pain was assessed by using visual analog scales (0-100 mm) at rest and during physiotherapy. Pain at rest was less in the EDA (n = 43) group than in the GA/PCA (n = 45) group (at 10 h: 11.8+/-12.9 vs. 28.4+/-17.1 [P< 0.001]; at 24 h: 14.3+/-11.7 vs. 24.0+/-17 [P<0.01]; in 48 h: 14.3+/-9.3 vs. 21.1+/-17.4 [P = 0.1]). Whereas EDA patients were deemed ready for discharge from the postanesthesia care unit earlier than GA/PCA patients (5.6+/-8.9 vs. 39.7+/-41.5 min), the actual discharge time was comparable. The median time for first passage of flatus was shorter in the EDA group than in the GA/PCA group (26 vs. 47 h). Nausea and vomiting were more common in the GA/PCA group than in the EDA group (16% vs. 28% and 11% vs. 22%, respectively), whereas hypotension (11% vs. 4%) and bradycardia (14% vs. 2%) were less frequent. Under the conditions of the present study, EDA with ropivacaine provided pain control after hip replacement superior to that provided by IV patient-controlled analgesia with morphine, particularly during the first 24 h. Both approaches to pain management were equally safe. IMPLICATIONS: Compared with general anesthesia and postoperative IV patient-controlled analgesia with morphine, epidural anesthesia and analgesia with the new local anesthetic ropivacaine enables patients to be discharged sooner from a postanesthesia care unit and provides superior pain relief during the first 24 h after hip replacement.